TRLS-04. NEAR INFRARED FLUORESCENT DYE LOCALIZES BRAIN METASTASIS PRIOR TO DURAL OPENING AND IS MORE SENSITIVE THAN WHITE LIGHT IN BRAIN METASTASIS SURGERY. (12th August 2019) - Buch, Love; Cho, Steve; Salinas, Ryan; Hussain, Jasmin; Lee, John
Abstract: INTRODUCTION: To improve surgical resection of brain tumors, our lab has pioneered a novel fluorescent dye technique, Second-Window Indocyanine-Green (SWIG), that relies on passive delivery and accumulation of indocyanine-green (ICG) in neoplastic tissue via the enhanced permeability and retention effect. We hypothesize that SWIG can provide early localization of brain metastasis prior to dural opening and can improve identification of surgical margins. METHODS: Subjects were prospectively enrolled in clinical trial after informed consent. Approximately 24 hours prior surgery, subjects were infused intravenously with 2.5mg/kg or 5mg/kg of ICG. Intraoperatively, a dedicated near-infrared (NIR) camera was used to detect ICG signal. After bone flap removal, the NIR imaging system was positioned above the presumed location of tumor. Additional NIR images were obtained after dural opening, corticectomy, and after conventional white-light surgical resection. RESULTS: We enrolled 50 patients with 51 total intraparenchymal brain metastases (23 lung, 7 breast, 8 GU/GI, 4 melanoma, and 7 others). Prior to dural opening, NIR signal was identified in 35 patients at an average depth of 4.3mm with SBR = 5.3 + 3.7. In the seven patients where NIR signal could not be identified prior to dural opening, tumor depth was an average of 8.4mm from cortical surface. Upon dural opening and tumor identification, all 51 tumors demonstrated strong NIR signal with SBR = 6.2 + 2.8. With white light alone, sensitivity/specificity/PPV/NPV for tumor detection was 83%, 94%, 98%, 57%. With NIR, sensitivity/specificity/PPV/NPV for tumor detection was 100%, 29%, 85%, 100%. DISCUSSION: NIR fluorophores are superior to visible light fluorophores in their depth of penetration. All contrast-enhancing brain metastasis accumulate ICG using our SWIG technique, and NIR fluorescence could be used to localize brain metastasis prior to dural opening. NIR fluorophores are likely to represent the next phase in tumor visualization given the rapid growth of fluorophores targeted to systemic cancers.